2022
DOI: 10.1155/2022/9709253
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Isolates and Antibacterial Resistance Patterns in a Patient with Acute Exacerbation of Chronic Obstructive Pulmonary Disease in a Tertiary Teaching Hospital, Southwest Ethiopia

Abstract: Introduction. Chronic obstructive pulmonary disease (COPD) is a major cause of chronic morbidity and mortality worldwide. The natural course of COPD is characterized by acute exacerbation. Infectious agents, particularly bacteria, cause exacerbation of COPD in the majority. This study aimed to determine the bacteriology and antibiotic resistance patterns among patients with acute exacerbations of COPD (AECOPD) at Jimma Medical Center. Methods. A cross-sectional study was conducted from March to October 2019. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 29 publications
3
11
2
Order By: Relevance
“…In addition, the difference between the different studies could be the fact that our study subjects were hospitalized patients and commonly with underlying diseases. But the MDR resistance rate was lower than the rate of antibiotic resistance patterns of bacterial isolates among patients with lower respiratory tract infection reported in the same study setting by Mussema et al 93.8% of the isolates were MDR and the resistance rates of gram-negative bacterial isolates were ranged from 88% to 80% to third and fourth-generation cephalosporin’s ( 18 ). This might be as a result of exposure to beta lactam medications repeatedly during recurrent exacerbations.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In addition, the difference between the different studies could be the fact that our study subjects were hospitalized patients and commonly with underlying diseases. But the MDR resistance rate was lower than the rate of antibiotic resistance patterns of bacterial isolates among patients with lower respiratory tract infection reported in the same study setting by Mussema et al 93.8% of the isolates were MDR and the resistance rates of gram-negative bacterial isolates were ranged from 88% to 80% to third and fourth-generation cephalosporin’s ( 18 ). This might be as a result of exposure to beta lactam medications repeatedly during recurrent exacerbations.…”
Section: Discussionmentioning
confidence: 74%
“…The resistance for these β-lactam antibiotics due to the production of β-lactamases is becoming a worldwide problem. These can be developed when bacterial gene mutate continuously in response to overuse or misuse of β-lactam antibiotics ( 18 , 29 ). In this study, the magnitude of ESBLs production was in agreement with study reported in Jimma Ethiopia 40.4% ( 30 ), higher than study reported in Addis Ababa Ethiopia 57.7% ( 31 ) and Nigeria 58.0% ( 32 ), and higher than study finding reported in Nepal 28.1% ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, variations in the distributions of the respiratory microbiota between various populations may be a contributing factor. 12 For example, the predominant isolated organism in one South Korean study 13 and another Ethiopian one 14 was Pseudomonas aeruginosa, while Klebsiella pneumoniae prevailed in an Indian study. 15 It was also noted that isolated organisms may vary between upper and lower respiratory tracts in patients with stable COPD and AECOPD.…”
Section: Introductionmentioning
confidence: 99%